The role of dispersive forces determining the energetics of adsorption in Ti zeolites. Issue 30 (30th September 2016) - Signorile, Matteo; Damin, Alessandro; Bonino, Francesca; Crocellà, Valentina; Lamberti, Carlo; Bordiga, Silvia
Abstract : Ti‐zeolites are interesting materials because of their key role in partial oxidation reactions, as well as under a fundamental point of view being regarded as single site catalysts. Both experimental and computational approaches have been widely applied to the characterization of their active sites, reaching a level of knowledge unmatchable by most other important catalysts. However, several questions are still open, being a proper energetic simulation of the adsorption process of simple molecules, fitting with the experimental outcomes, still missing. The present work wants to underline the role of dispersive forces in correctly determining the adsorption energies of H2 O and NH3 in Ti chabazite: first dispersive contributions have been included through an ONIOM scheme, comparing the results from semiempirical Grimme scheme and fully ab initio MP2. Being the key contribution of dispersion proved, a fully periodic, Grimme dispersions inclusive approach has been applied, coming to results close to the experimental values. © 2016 Wiley Periodicals, Inc. Abstract : Dispersive interactions allow the proper description of adsorption energy for water and ammonia, whereas a purely electronic description largely underestimates the interaction energy.